Urodynamic Evaluation of Benign Prostatic Hyperplasia Patients with Urinary Retention and Small Prostate Volume - Budaya, Taufiq Nur; Daryanto, Besut (International Journal of Psychosocial Rehabilitation, 2020)
The relevance of prostate size in the pathophysiology of lower urinary tract symptom and urinary retention in BPH patients is still controversial. We evaluated the urodynamic findings in patients with Benign Prostate Hyperplasia (BPH) and urinary retention with small prostate volumes (20-40cc). The 96 patients aged older than 50 years and clinically diagnosed with BPH and urinary retention with prostate volume 20-40 cc were enrolled in this study. We compared all findings in urodynamic study, age and prostate volume according to the presence of Bladder outlet obstruction (BOO) or not. Mean prostate volume was 31,12±4,7ml. BOO was the main finding, affecting 56 (58.3%) patients, followed by non-BOO 40 (41,7%) patients. The maximum cystometric-capacity (CCmax), compliance, maximum flow rate (Qmax) and residual urine was significantly higher in non-BOO compared to BOO patients (p 0,000, p 0,023, p 0,009 and p 0,020 respectively). The detrusor-pressure during CCmax (PdetCCmax) and during maximum urinary-flow (PdetQmax) were significantly higher in BOO compared to non BOO patients (p 0,000 and p0,000 respectively). All (100%) non-BOO patients experienced detrusor underactivity (DU), meanwhile only 42% of BOO patients experienced detrussor underactivuty (DU). Thirty-five percent of BOO patients had detrusor overactivity (DO). No significant differences in age and prostate volume, were observed between the two groups. Almost half of the patients with urinary retention and small prostates were not obstructed and all of them experienced either DO or DU as the basis of their voiding symptoms. Our results emphasize the value of urodynamic in this population, especially when invasive treatments are being considered.